2014
DOI: 10.4014/jmb.1401.01009
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Community Migration in the Ripening of Doenjang, a Traditional Korean Fermented Soybean Food

Abstract: Doenjang, a traditional Korean fermented soybean paste, is made by mixing and ripening meju with high salt brine (approximately 18%). Meju is a naturally fermented soybean block prepared by soaking, steaming, and molding soybean. To understand living bacterial community migration and the roles of bacteria in the manufacturing process of doenjang, the diversity of culturable bacteria in meju and doenjang was examined using media supplemented with NaCl, and some physiological activities of predominant isolates w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
80
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 79 publications
(91 citation statements)
references
References 24 publications
7
80
0
1
Order By: Relevance
“…Jeong et al. () found that Enterococcus faecalis and Enterococcus faecium were the predominant Enterococcus in meju samples. As enterococci are an essential part of the microflora of humans and animals, we can speculate that Enterococcus faecalis in da‐jiang comes from humans during the process of mashing and molding the steamed soybean (Jeong, Jeong, & Lee, ).…”
Section: Discussionmentioning
confidence: 99%
“…Jeong et al. () found that Enterococcus faecalis and Enterococcus faecium were the predominant Enterococcus in meju samples. As enterococci are an essential part of the microflora of humans and animals, we can speculate that Enterococcus faecalis in da‐jiang comes from humans during the process of mashing and molding the steamed soybean (Jeong, Jeong, & Lee, ).…”
Section: Discussionmentioning
confidence: 99%
“…In our previous analysis of the cultivable bacterial community during the ripening of doenjang, a traditional fermented soybean food, coagulase-negative staphylococci (CNS) species, including Staphylococcus succinus , were isolated as a dominant bacterial group (1). In our successive study to select potential CNS starters for Korean fermented soybean foods, S. succinus isolates were identified as promising candidates in terms of safety, as well as technological functionality (2).…”
Section: Genome Announcementmentioning
confidence: 99%
“…Lactic acid bacteria including enterococci and coagulase‐negative staphylococci (CNS) have been identified as the predominant group of bacteria together with bacilli. We analyzed the microbiota of meju and doenjang using culture‐dependent methods and isolated numbers of bacilli, enterococci, and CNS (Jeong et al, ). In the following assessments of the safety, proteolytic and lipolytic enzyme activities, and salt tolerance of isolates, followed by analyses of the volatile compounds produced from their soybean cultures (Jeong, Heo, et al, ; Jeong, Jeong, & Lee, ; Jeong, Jeong, et al, ; Jeong, Lee, Her, Lee, & Lee, ), three strains of Bacillus licheniformis , Enterococcus faecium , and Staphylococcus succinus have been selected.…”
Section: Introductionmentioning
confidence: 99%